Tricks For Excellent Studying: The Impact Of Study Habits And Learning Environment On Student Achievement At Mts Darul Hikmah Langkap Burneh Bangkalan - Amrulloh; Didit Darmawan (Hikamatzu | Journal of Multidisciplinary, 2024)
Education is one of the key factors in character formation and development of student potential. At the secondary education level, student achievement factors are a concern. Student learning achievement is not only influenced by internal factors such as study habits, but also by external factors such as the learning environment. This research aims to analyze the influence of study habits and learning environment on student learning achievement at MTs Darul Hikmah Langkap Burneh Bangkalan. This research uses a quantitative approach with regression analysis methods. The research population involved all students at MTs Darul Hikmah Langkap Burneh Bangkalan, with a sample of 30 students selected by random stratification. Data analysis was carried out using descriptive statistics and regression analysis. Good study habits have been proven to have a positive effect on achieving high grades. A clean, comfortable learning environment and positive social interactions also have a positive impact on learning achievement. It is hoped that these findings will guide the development of more effective educational programs